Pengaruh Financial Distress, Pertumbuhan Perusahaan Klien, Ukuran Kap, Dan Audit Delay Terhadap Auditor Switching - Faradina Zikra; Efrizal Syofyan (Universitas Negeri Padang, 2019)
This study aims to examine the effect of financial distress, client company growth, KAP size and audit delay on auditor switching. This study is classified as comparative causal research. The population in this study are mining companies listed on the Indonesia Stock Exchange period of 2013 to 2017. By using purposive sampling method, there were 85 companies as the research samples. Auditor switchingare measured by dummy. The type of data used is secondary data obtained from www.idx.co.id and use logistic regression analysis. The results of this study indicate that financial distress, client company growth, KAP size and audit delay have no influence on auditor swtiching..